Contests for Status - Benny Moldovanu; Aner Sela; Xianwen Shi (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
We study the optimal design of organizations under the assumption that agents in a contest care about their relative position. A judicious definition of status categories can be used by a principal in order to influence the agents' performance. We first consider a pure status case where there are no tangible prizes. Our main results connect the optimal partition in status categories to various properties of the distribution of ability among contestants. The top status category always contains an unique element. For distributions of abilities that have an increasing failure rate, a proliferation of status classes is optimal, while in other cases the optimal partition involves some coarseness. Finally, we modify the model to allow for status categories that are endogenously determined by monetary prizes of different sizes. If status is solely derived from monetary rewards, we show that the optimal partition in status classes contains only two categories.
urn:nbn:de:bvb:19-epub-13412-8
Keywords: 330